Yellow Cart Feature on Tiktok as a Medium to Attract Purchase Interest - Nabilla Riefa Tunisya; Rachel Diandra Chairunnisa; J. A. Wempi (Jurnal Indonesia Sosial Sains, 2024)
The number of social media users worldwide reached 4.76 billion in January 2023, with 167 million active users in Indonesia. This study aims to understand how the yellow basket feature on TikTok attracts consumers' buying interest, using a qualitative approach through interviews and literature studies. The results show that this feature is effective in attracting buyers through factors such as attractive video displays, product promos, and ease of transaction processes. The promos offered, the attractive display of product videos, and the ease of transactions are the main factors that increase buying interest. In conclusion, the yellow cart feature on TikTok affects consumers' buying interest by providing ease of transactions and attractive promotions without the need to switch to other platforms.